2012
DOI: 10.1186/cc11355
|View full text |Cite
|
Sign up to set email alerts
|

Association of gender with outcomes in critically ill patients

Abstract: IntroductionThe influence of gender on mortality and other outcomes of critically ill patients is not clear. Different studies have been performed in various settings and patient populations often yielding conflicting results. We wanted to assess the relationship of gender and intensive care unit (ICU) outcomes in the patients included in the Acute Physiology and Chronic Health Evaluation (APACHE) IV database (Cerner Corporation, USA).MethodsWe performed a retrospective review of the data available in the APAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
98
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 43 publications
(52 reference statements)
14
98
1
2
Order By: Relevance
“…Similar findings have been reported previously, 2,7,13 although some controversy remains. [14][15][16] The reasons women may have a higher mortality than men during a critical illness are poorly understood, and clinical studies [17][18][19] have shown that women have higher mortality rates than men do despite biological evidence of the protective effect of estrogens on both immune function and cardiovascular responses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings have been reported previously, 2,7,13 although some controversy remains. [14][15][16] The reasons women may have a higher mortality than men during a critical illness are poorly understood, and clinical studies [17][18][19] have shown that women have higher mortality rates than men do despite biological evidence of the protective effect of estrogens on both immune function and cardiovascular responses.…”
Section: Discussionsupporting
confidence: 90%
“…We conducted a retrospective study to determine if delays in ICU admission and severity of illness before ICU admission differed between men and women who were already hospitalized and if ICU mortality differed according to sex between medical and surgical patients. We also sought to confirm previous reports that differences in mortality between the sexes are more pronounced in younger patients 7 and in patients who were less severely ill. 8 …”
mentioning
confidence: 67%
“…Mahmood et al (12) explored the relation between age and clinical course and found no significant difference between female and male patients who were aged 50 years and older, but the mortality at the age of 50 years was lower in female patients than in male patients. Jacobson et al (13) conducted a prospective observational cohort with the patients internalized in the ICU for a 3-year period; with sepsis in the first 24 h, no correlation was found between mortality, hospitalization duration, and gender.…”
Section: Discussionmentioning
confidence: 99%
“…But, no difference in mortality was shown in patients with CAD, sepsis or trauma. [12] With respect to epidemiology, Sakr et al reported more male admissions compared to females and even the prevalence of sepsis was lower in females. But the incidence of ICU mortality was more with female patients with severe sepsis.…”
mentioning
confidence: 99%